PENGGUNAAN BAHASA IKLAN DALAM PROMOSI DESA WISATA DI KABUPATEN SUMBAWA PROPINSI NUSA TENGGARA BARAT - Najamudin, Najamudin; Putra, Erwinsyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The purpose of this study was to describe the use of advertising language in the promotion of tourism villages in Sumbawa district, West Nusa Tenggara province. Methods This research is using qualitative methods. Data collection techniques used through observation, interviews and documentation. The data analysis technique used the theory of Miles and Huberman, namely the technique of reducing, displaying data and verifying data.The results of the analysis, the use of advertising language in tourism promotion which consists of four tourist villages in Sumbawa Regency includes, (1) The use of advertising language in the promotion of Agal waterfall tourism in Marenteh village, shows language that is informative and language that is evocative and language is persuasive. (2) The use of advertising language for Liang Petang Cave tourism in Batu Tering Village is the use of advertising language that is persuasive and informative. Furthermore, the mysterious burrow buccal tourism advertisement in Marente village, the use of advertising language used is persuasive. (3) The use of advertising language in the promotion of Gili Bedil Island tourism in Labuan Bajo village is an informative advertising language. (4) The use of the language used in the promotion of Moyo Island tourism in Labuan Aji village is an informative advertising language.